2015
DOI: 10.1039/c5cc05307b
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured high-performance dielectric block copolymers

Abstract: A new type of insulating-conductive block copolymer was synthesized by metathesis polymerization. The copolymer can self-assemble into unique nanostructures of micelles or hollow spheres. It exhibits a high dielectric constant, low dielectric loss, and high stored/released energy density due to the strong dipolar and nano-interfacial polarization contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Subsequently, another groundbreaking result was reported by Buchmeiser and co-workers, who demonstrated the first example of CP using easy-to-use, modified Grubbs catalysts containing electron-withdrawing ligands, such as the trifluoroacetate ligand, and showed that these catalysts produced conjugated polyenes with five-membered ring repeat units exclusively via α-addition. , Recently, our group reported a highly efficient living CP of 1,6-heptadiyne derivatives using third-generation Grubbs catalyst to produce conjugated polyenes with exclusive five-membered ring backbones with excellent molecular weight control and narrow polydispersity index (PDI) . With this catalyst, the syntheses of fully conjugated block copolymers and other functional polyenes were also possible. However, the formation of conjugated polyenes with six-membered rings by selective β-addition using Ru catalysts has not been achieved. Instead, Ru catalysts could only produce polyenes with six-membered rings from various 1,7-octadiyne monomers by selective α-addition .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequently, another groundbreaking result was reported by Buchmeiser and co-workers, who demonstrated the first example of CP using easy-to-use, modified Grubbs catalysts containing electron-withdrawing ligands, such as the trifluoroacetate ligand, and showed that these catalysts produced conjugated polyenes with five-membered ring repeat units exclusively via α-addition. , Recently, our group reported a highly efficient living CP of 1,6-heptadiyne derivatives using third-generation Grubbs catalyst to produce conjugated polyenes with exclusive five-membered ring backbones with excellent molecular weight control and narrow polydispersity index (PDI) . With this catalyst, the syntheses of fully conjugated block copolymers and other functional polyenes were also possible. However, the formation of conjugated polyenes with six-membered rings by selective β-addition using Ru catalysts has not been achieved. Instead, Ru catalysts could only produce polyenes with six-membered rings from various 1,7-octadiyne monomers by selective α-addition .…”
Section: Introductionmentioning
confidence: 93%
“…Initially, ill-defined catalysts, such as Ziegler-type, MoCl 5 , and WCl 6 , were used . Then, the development of homogeneous Schrock catalysts provided the first groundbreaking contribution to the understanding of the mechanism of CP and the structural information for the resulting conjugated polyenes. Recently, the scope of CP was greatly expanded with the development of Ru-based Grubbs catalysts and modified Grubbs catalysts because they were highly active, very user-friendly, and tolerant to air, moisture, and many functional groups. …”
Section: Introductionmentioning
confidence: 99%
“…Besides issues also known to occur for SEC on homopolymers, e.g. associated with aggregation 2 or chemical dissimilarity with the calibration standard, [3][4][5] new challenges appear due to the mere fact that the different blocks themselves have different properties and solvation. Consequently, their interaction with both the mobile and stationary phases, as well as their resemblance with the calibration standard, is per definition different.…”
Section: Introductionmentioning
confidence: 99%
“…However, several intrinsic defects, including brittleness, weak dielectric strength, difficult to process and/or extremely high processing temperature, have encountered when using these inorganic ceramics1718. In recently years, high performance polymers and polymer based composites as ideal alternative candidates for these applications have been intensively investigated owing to their fascinating properties1920212223242526.…”
mentioning
confidence: 99%